Carbon/Inorganic Hybrid Nanoarchitectures as Carriers for Signaling Elements in Electrochemical Immunosensors: First Biosensor for the Determination of the Inflammatory and Metastatic Processes Biomarker RANK‐ligand. Issue 3 (5th February 2020) - Valverde, Alejandro; Serafín, Verónica; Montero‐Calle, Ana; González‐Cortés, Araceli; Barderas, Rodrigo; Yáñez‐Sedeño, Paloma; Campuzano, Susana; Pingarrón, José M.
Abstract: This work reports the development of the first integrated electrochemical immunosensor for the determination of the ligand receptor activator nuclear factor‐κB (RANKL), a biomarker that plays an important role in the regulation of bone resorption process and, as reported recently, in oncology by modulating the immune system response facilitating the tumor growth and metastatic process during cancer development. The developed platform involves a sandwich‐type immunoassay with covalent immobilization of biotinylated capture antibodies onto streptavidin/4‐aminobenzoic acid ( p ‐ABA) grafted screen‐printed carbon electrodes (bCAb‐Strep/ p ‐ABA‐SPCE) and the use of an hybrid nanomaterial composed of gold nanoparticles (AuNPs) and multi‐walled carbon nanotubes (MWCNTs) as nanocarrier of multiple detector antibody and HRP molecules. Amperometric detection with the H2 O2 /hydroquinone (HQ) system allowed the construction of a linear calibration plot for RANKL standards between 10.4 and 1, 000 pg mL −1 with a LOD of 3.1 pg mL −1 . The determination implied simple handling protocols and short assay times. The developed immunosensor was applied to the determination of RANKL in human serum of patients diagnosed with colorectal cancer (CRC) or rheumatoid arthritis (RA). Each determination required only 5 μL of undiluted serum and took less than 2 h counting since the preparation of blocked‐bCAb‐Strep/ p ‐ABA‐SPCE. Abstract : Quick detection : We report the first integrated electrochemical immunosensor for the determination of the ligand receptor activator nuclear factor‐κB (RANKL), a biomarker that plays an important role in the regulation of bone resorption process and in oncology. The developed immunosensor requires only 5 μL of undiluted serum and takes less than 2 h for the determination of RANKL in human serum of patients diagnosed with colorectal cancer or rheumatoid arthritis.